2022
DOI: 10.1021/acs.jafc.2c04817
|View full text |Cite
|
Sign up to set email alerts
|

Nuciferine Protects Against High-Fat Diet-Induced Hepatic Steatosis via Modulation of Gut Microbiota and Bile Acid Metabolism in Rats

Abstract: Our previous study showed that nuciferine (NF) attenuated non-alcoholic fatty liver disease (NAFLD), which is attributed to a high-fat diet (HFD) through reinforcing intestinal barrier functions, regulating lipid metabolism, and improving inflammation. To clarify whether other mechanisms contribute to the anti-NAFLD efficacy of NF, the present study investigated the influence of NF on bile acid (BA) metabolism and gut microbiota in HFD-fed rats. The data demonstrated that NF changed the composition of colonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…55 Nuciferine changes the composition of colonic BA, increases the level of conjugated Bas, inhibits ileal FXR signal transduction, upregulates the expression of CYP7A1, promotes BA synthesis, inhibits BA reabsorption, and promotes fecal BA excretion, thereby alleviating NAFLD. 56 The hepatic FXR-liver X receptor α (LXRα) pathway and the intestinal FXR-FGF15 pathway work together in the synthesis of BA. 57 Our previous research has shown that berberine and evodiamine, the main active ingredient of ZYP, effectively increase the expression of LXRα and CYP7A1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Nuciferine changes the composition of colonic BA, increases the level of conjugated Bas, inhibits ileal FXR signal transduction, upregulates the expression of CYP7A1, promotes BA synthesis, inhibits BA reabsorption, and promotes fecal BA excretion, thereby alleviating NAFLD. 56 The hepatic FXR-liver X receptor α (LXRα) pathway and the intestinal FXR-FGF15 pathway work together in the synthesis of BA. 57 Our previous research has shown that berberine and evodiamine, the main active ingredient of ZYP, effectively increase the expression of LXRα and CYP7A1.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, l -theanine intervention produced low FXR and FGF15 expression and high CYP7A1 expression, reduced TC, TG, and LDL-C content, increased HDL-C content, and improved lipid metabolism . Nuciferine changes the composition of colonic BA, increases the level of conjugated Bas, inhibits ileal FXR signal transduction, upregulates the expression of CYP7A1, promotes BA synthesis, inhibits BA reabsorption, and promotes fecal BA excretion, thereby alleviating NAFLD …”
Section: Discussionmentioning
confidence: 99%
“…Nuciferine has been found to alleviate alcoholic fatty liver in Sprague-Dawley rats fed with a high-fat diet, reduce the level of Lactobacillus , reduce BSH production, reduce 7α-dehydroxylation genus, and increase taurine metabolism-related genus. 76 In addition, Penthorum chinense Pursh. extract (PCPE) was also found to improve the NAFLD of C57BL/6J mice by reducing the relative abundance of BSH-producing bacteria, especially Lactobacillus .…”
Section: Mechanism Of Action Mediated By Polyphenolsmentioning
confidence: 99%
“…Studies have found that natural medicines from plants are effective in reducing inflammation and restoring intestinal flora. [8][9][10] However, these natural drugs have the corresponding disadvantages of weak activity and low yield, which hamper their application. 11,12 By breaking down the molecular structure of natural drugs, some products with the same structure can be obtained by artificial synthesis.…”
Section: Introductionmentioning
confidence: 99%